PENJATUHAN PIDANA BERSYARAT BAGI KORUPTOR DALAM PERSPEKTIF UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Dwi Setyo Budi Utomo; Widodo T. Novianto; Supanto (HUKUM PEMBANGUNAN EKONOMI, 2017)
AbstractThis articles aimed at to analyze the provision of criminal conditional for cesspool in perspective the fight against of corruption in Indonesia. The kind of research in this article is doctrinal, while seen from its shape including research evaluative sense and analyzing of using analysis quantitative. That the judge in dropped decisions based on laws and confidence judge. Basis of consideration for judges in criminal conditional drop in matters of corruption is based on sociological factors/non-yuridis so the provision conditional criminal in matters of corruption is more dependent on conscience judge whether to drop criminal. conditional or not. Criminal conditional not arranged in the Act of Corruption Eradication but set In Article 14a Book I the Book the Act of Criminal Law about the rules general. Based on Article 103 the Book the Act of Criminal Law, Article 14a as a provision general may shall also apply to a statute outside the Book the Act of Criminal Law including the act of corruption eradication except otherwise stated in this law. The Act of Corruption Eradication own that no decree enactment of criminal conditional, so based on Article 14a the Book the Act of Criminal Law judge have a chance to drop criminal conditional to an offender of corruption. Recommendations is : 1) the judge in its consideration dropped criminal on the corruption must be more due observance to the provision laws and regulations so that created an award the quality meet the sense of justice, profit or legal certainty. 2) Expected for judges to observe rules and regulations in dropped criminal for creative corruption though judge are free to drop criminal to avoid possible disparity the award.Keywords: Conditional Criminal; Corruption; Judge.AbstrakArtikel ini bertujuan untuk menganalisis penjatuhan Pidana Bersyarat bagi koruptor dalam prespektif upaya pemberantasan tindak pidana korupsi di Indonesia. Jenis penelitian dalam artikel ini adalah doktrinal, sedangkan dilihat dari bentuknya termasuk penelitian evaluatif dan analisis datanya menggunakan analisis kuantitatif. Bahwa Hakim dalam menjatuhkan putusan didasarkan pada undang-undang yang berlaku dan keyakinan hakim. Dasar pertimbangan bagi hakim dalam menjatuhkan pidana bersyarat dalam perkara tindak pidana korupsi adalah didasarkan pada faktor sosiologis/non-yuridis sehingga penjatuhan pidana bersyarat dalam perkara tindak pidana korupsi ini lebih tergantung pada hati nurani hakim apakah mau menjatuhkan pidana bersyarat atau tidak. Pidana Bersyarat tidak diatur dalam UU PTPK melainkan diatur dalam Pasal 14a Buku I KUHP tentang Ketentuan Umum. Berdasarkan Pasal 103 KUHP, Pasal 14a sebagai ketentuan umum dapat berlaku juga untuk undang-undang diluar KUHP termasuk UU PTPK kecuali ditentukan lain dalam undang-undang tersebut. UU PTPK sendiri tidak ada larangan diterapkannya pidana bersyarat, sehingga berdasarkan Pasal 14a KUHP hakim memiliki peluang untuk menjatuhkan pidana bersyarat kepada pelaku tindak pidana korupsi. Rekomendasinya adalah : 1) Hakim dalam pertimbangannya menjatuhkan pidana terhadap kasus korupsi harus lebih memperhatikan ketentuan peraturan perundang-undangan yang berlaku agar kelak menciptakan suatu putusan berkualitas yang memenuhi rasa keadilan, kemanfaatan dan kepastian hukum. 2) Diharapkan bagi hakim untuk mematuhi peraturan perundang-undangan yang berlaku dalam menjatuhkan pidana bagi pelaku korupsi walaupun hakim memiliki kebebasan dalam menjatuhkan pidana agar tidak terjadi disparitas putusan.Kata kunci: Pidana Bersyarat; Korupsi; Hakim